WISATA ALAM KABUPATEN LIMA PULUH KOTA MEMBUKA PELUANG USAHA BAGI MASYARAKAT (JURNAL SPASIAL, 2016)
The purpose of this research is to determine the nature contained and dispersed in the District Fifty Cities that can open up business opportunities for the local population. Natural state is owned by the City District Fifty is a natural resource that has been built and developed into a tourist attraction presented by the landscape to the audience, so it has a charm that is intended as a tourist. The method used in this research is descriptive qualitative, which intends to describe and narrate stretch of natural attractions located in the district of Lima City. The results that this is a reference nature to be visited by the visitors and the benefit and satisfaction of natural attractions Fifty Cities and counties get a good service to menikmat so that the service stepping indulgence for the nature lovers. With the ministry's stepping opens opportunities for people who are around him, both in terms of sauvenir and cafes that serve regional specialties Fifty Cities districts themselves.Keywords: Object, Tour, Landscape.